2014
DOI: 10.1111/jsm.12675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Genito-Pelvic Pain in Pregnancy and Postpartum: The Prospective Impact of Fear Avoidance

Abstract: Introduction There is limited knowledge regarding the symptom profile of genito-pelvic pain in pregnancy and postpartum, and potential psychosocial predictors of this pain. Prior studies have reported a positive association between prepregnancy pain and postpartum genito-pelvic pain. Greater fear avoidance has been associated with increased genital pain intensity in women, unrelated to childbirth. This relationship has not been examined prospectively in a postpartum population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
0
25
1
Order By: Relevance
“…Half the women with these symptoms were worried, and such worries might affect the further progression of the pregnancy. 13,30 The large Norwegian Mother and Child Cohort showed that severe pelvic girdle pain combined with emotional distress was associated with non-recovery after delivery. 30 Furthermore, pain-related anxiety in pregnancy has been shown to be associated with greater pain intensity and unpleasantness of postpartum genital-pelvic pain.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Half the women with these symptoms were worried, and such worries might affect the further progression of the pregnancy. 13,30 The large Norwegian Mother and Child Cohort showed that severe pelvic girdle pain combined with emotional distress was associated with non-recovery after delivery. 30 Furthermore, pain-related anxiety in pregnancy has been shown to be associated with greater pain intensity and unpleasantness of postpartum genital-pelvic pain.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…30 Furthermore, pain-related anxiety in pregnancy has been shown to be associated with greater pain intensity and unpleasantness of postpartum genital-pelvic pain. 13 It is possible that some of these women could be helped earlier and maybe not suffer from lack of recovery from pelvic girdle pain postpartum, if addressed at the first prenatal care visit.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal changes (Koshaka, 1998;Kitzinger, 1983); Nausea and fatigue (Kitzinger, 1983); Weight gain and big belly (Erol, 2007); Big breasts and breast pain (Kitzinger, 1983); Painful intercourse (Glowacka, 2014); Anatomical changes in the urinary tract and pelvic floor (Change, 2014); Pregnancy age and number of pregnancies and deliveries (Eryilmaz, 2004;Tosun, 2014).…”
Section: Biological Factorsmentioning
confidence: 99%
“…This pelvic congestion may lead to a marked increase in the intensity of a woman's orgasm. Many women who never have experienced orgasm during intercourse have their first orgasms during this time; women who previously have been orgasmic may have the experience of multiple orgasms [30].…”
Section: Biomedical Psychological and Relationship Factorsmentioning
confidence: 99%